2016
DOI: 10.1590/2238-38752016v618
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities and the Brazilian New Democracy: Income Distribution Between Classes in Recent Decades

Abstract: The final years of military government in Brazil were marked by a growing expectation that the transition to the democratic regime would be able -or sufficient -to eliminate the main problems afflicting Brazilian society, including poverty, corruption, violence, the quality and reach of public services, inflation, inequalities, and so on (Fausto, 1994). However, the recent literature on Brazil -whether in Sociology, Political Science or Economics, or even the reports circulating in the mass media over recent y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(6 reference statements)
0
3
0
2
Order By: Relevance
“…Em seguida, temos a classe sócio-ocupacional do chefe do domicílio em que reside o jovem. Neste trabalho utilizaremos o esquema de classes desenvolvido por entre classes (Salata, 2016), o que também pode vir a contribuir para a redução do efeito de origem sobre as chances de acesso. 10.…”
Section: Hipóteses Dados E Métodosunclassified
See 1 more Smart Citation
“…Em seguida, temos a classe sócio-ocupacional do chefe do domicílio em que reside o jovem. Neste trabalho utilizaremos o esquema de classes desenvolvido por entre classes (Salata, 2016), o que também pode vir a contribuir para a redução do efeito de origem sobre as chances de acesso. 10.…”
Section: Hipóteses Dados E Métodosunclassified
“…Finalmente, é plausível pensarmos que a redução das desigualdades econômicas entre classes, ocorrida na última década (Salata, 2016(Salata, , 2018, tenha também contribuído para a redução das desigualdades de acesso ao Ensino Superior. Afinal, como vimos, uma diminuição das desigualdades econômicas seria capaz de reduzir os diferenciais de custos, entre classes, associados à opção dos jovens por continuar estudando (Breen e Goldthorpe, 1997).…”
Section: Conclusõesunclassified
“…Elgar et al [ 38 ] also observed that the increase in income inequality was associated with the increase in cases and mortality rates due to COVID‐19 in 84 countries, including Brazil. For many decades, Brazil has been showing a high level of income inequality [ 39 ] that sets the country the challenge of two epidemics: COVID‐19 and social inequality itself, which puts millions of Brazilians at risk of returning to extreme poverty [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of Brazil as a country in transition, this discussion holds potential for conflict due to its high levels of inequality and economic and politic instability. A focus on consuming 'better' could facilitate a period of slow growth (Victor, 2010), providing a transition period allowing private sector actors and citizens to reduce their social and environmental impact while tackling the vast array of interwoven social problems existent in Brazil (Salata, 2016).…”
Section: Consumption Practices In Brazil: Status Quo and What Lies Aheadmentioning
confidence: 99%